Metamorphosis of citizenship education: Ignizing national awareness of the younger generation - Purwadi, Danang; Saliman, Saliman; Umar, Umar (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
This article discusses nationalism among the young generation, a sense of nationalism is inherent in a person since birth, in the era of globalization, advances in information technology have a good impact on the progress of the nation but it does not rule out the possibility of having a bad impact on the younger generation. This study uses a qualitative approach with in-depth interviews and content analysis to explore the perceptions and experiences of students and educators related to civics learning. The results of the study indicate that Civic Education that combines theory and practice, involves active student participation, and integrates the values of Pancasila and the history of the nation, can increase the awareness of nationalism of the younger generation. Researchers focus more on discussing the role of educational institutions or schools. Through Civic Education which aims to make citizens feel proud as Indonesian citizens and foster a sense of love for the homeland and the younger generation has a sense of shared destiny so that they care and are sensitive to the problems faced by the country. This study uses a literature analysis approach to explore the impact of civics learning on the formation of national values, loyalty, and active participation in political and social life. This article also considers effective learning strategies in increasing awareness of the national identity of the younger generation. The results of this analysis are that civic education that focuses on understanding history, democratic values, and involvement in social activities can shape the nationalist attitude of the younger generation. Interactive learning, the habit of critical discussion, and the use of educational technology also have a positive impact on building a strong sense of national identity in the younger generation.